IMSI catchers: hacking mobile communications. Issue 2 (February 2017) - Lilly, Andy
Abstract : You're travelling, working on a new deal that's just about to close. You're involved in the final negotiations. You need to check a few points with colleagues back at base. You call them from a quiet place, away from eavesdroppers, from your mobile. But what about electronic eavesdroppers? These days a voice call is just another piece of data and it can be easily intercepted without you ever knowing. The apps you use on your mobile devices might claim to be secure – but is the device itself? What might it be giving away about you? The way our mobile networks function means that information can be intercepted and harvested by so-called IMSI catchers. This could have a significant impact on your security and privacy. So what are these devices, what dangers do they pose and how can you protect yourself? Andy Lilly of Armour Communications provides some answers.